The Fashion of Syntax: Exploring the Function of Subordinate Clauses as Adjuncts in Vogue Magazine - Fasha Egi Mulyana, Putu Galuh; Putu Devi Maharani (Universitas Cokroaminoto Palopo, 2025)
This study examines the role of subordinate clauses as adjuncts in complex sentences from the